Prognosis, Controversies and Assessment of Bone Erosion or Invasion of Oral Squamous Cell Carcinoma - Ahmed Ata Alfurhud (Diagnostics)
Objectives: To discuss the prognostic outcomes, controversies and assessment of bone erosion or invasion of oral squamous cell carcinoma (OSCC). Methods: A structured literature review was conducted to critically analyse relevant evidence. The Web of Science database was searched using specific keywords aligned with the review question. After identifying initial studies, their references were also reviewed to include any additional relevant publications, ensuring a comprehensive evaluation of the available evidence. Results: The search identified 11 relevant studies, including 5 from the initial search and 6 from reference review. The significance of bone involvement is unclear in OSCC, with varying definitions of cortical bone erosion and medullary bone infiltration contributing to conflicting results regarding the prognostic significance of bone involvement. The majority of evidence stems from retrospective cohort studies without clear study criteria and a lack of power to draw valid conclusions. Conclusions: There are currently a lack of high-quality studies assessing bone invasion in OSCC. While there appears to be some evidence that medullary bone infiltration is prognostic, further well-designed studies are warranted.